Analysis of Protein Palmitoylation Reveals a Pervasive Role in Plasmodium Development and Pathogenesis - Jones, Matthew L. (Cell Press, 2012)
Asexual stage Plasmodium falciparum replicates and undergoes a tightly regulated developmental process in human erythrocytes. One mechanism involved in the regulation of this process is posttranslational modification (PTM) of parasite proteins. Palmitoylation is a PTM in which cysteine residues undergo a reversible lipid modification, which can regulate target proteins in diverse ways. Using complementary palmitoyl protein purification approaches and quantitative mass spectrometry, we examined protein palmitoylation in asexual-stage P. falciparum parasites and identified over 400 palmitoylated proteins, including those involved in cytoadherence, drug resistance, signaling, development, and invasion. Consistent with the prevalence of palmitoylated proteins, palmitoylation is essential for P. falciparum asexual development and influences erythrocyte invasion by directly regulating the stability of components of the actin-myosin invasion motor. Furthermore, P. falciparum uses palmitoylation in diverse ways, stably modifying some proteins while dynamically palmitoylating others. Palmitoylation therefore plays a central role in regulating P. falciparum blood stage development.